2021
DOI: 10.5009/gnl210224
|View full text |Cite
|
Sign up to set email alerts
|

Management of Helicobacter pylori Infection: A Comparison between Korea and the United States

Abstract: Helicobacter pylori has been well known to cause gastritis, peptic ulcers, mucosa-associated lymphoid tissue, and gastric cancer. The importance of H. pylori eradication has been emphasized; however, the management of H. pylori infection is difficult in clinical practice. In both Eastern and Western countries, there has been a constant interest in confirming individuals who should be tested and treated for H. pylori in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Contrarily, persistent atrophic gastritis and cancer are brought on by low gastric acid output. [73][74][75][76][77][78][79] Patients with H. pylori infection had significantly higher levels of acid production and duodenal ulceration, suggesting that acid plays a crucial role in developing gastric mucosal ulcers. It has been demonstrated that a low pH (very acidic pH) enhances NF-kB binding caused by H. pylori.…”
Section: Chemistryselectmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, persistent atrophic gastritis and cancer are brought on by low gastric acid output. [73][74][75][76][77][78][79] Patients with H. pylori infection had significantly higher levels of acid production and duodenal ulceration, suggesting that acid plays a crucial role in developing gastric mucosal ulcers. It has been demonstrated that a low pH (very acidic pH) enhances NF-kB binding caused by H. pylori.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Antrum‐predominant gastritis and duodenal ulcers are more likely to occur in people with high gastric acid output. Contrarily, persistent atrophic gastritis and cancer are brought on by low gastric acid output [73–79] . Patients with H. pylori infection had significantly higher levels of acid production and duodenal ulceration, suggesting that acid plays a crucial role in developing gastric mucosal ulcers.…”
Section: Gastro‐protective Activities Of a Marmaelosmentioning
confidence: 99%
“…Global comparison of the proportion of antimicrobial-resistant Helicobacter pylori strains. Data were obtained from reports published since 2012 [45][46][47][48][49][50][51][52][53][54]. Multidrug-resistant strains were defined as those resistant to at least two antimicrobial agents.…”
mentioning
confidence: 99%
“…While the cure for H. pylori after treatment can be assessed using the 13C-urea breath test (UBT) or stool antigen test at least 4 weeks after treatment, until recently, guided therapy necessitated endoscopic diagnosis with biopsy-based methods that required the intervention of gastroenterologists [ 10 ]. The recent development and excellent performance of several real-time PCR techniques to detect Helicobacter pylori infection and clarithromycin resistance mutations in non-invasive samples (patient stool) provide general practitioners with a tool that can be used in routine diagnostic situations [ 11 ].…”
mentioning
confidence: 99%